Colorimetric test strip cassette readout with a smartphone for on-site and rapid screening test of carbamate pesticides in vegetables - Rakkhun, Waraporn; Jantra, Jongjit; Cheubong, Chehasan; Teepoo, Siriwan (My University, 2022)
A test strip cassette integrated with a smartphone detector was developed for the colorimetric detection of carbamate pesticides in vegetables. The influence of various experimental conditions was examined for the detection of the optimum analytical performance of the test strip cassette. The test strip cassette detection of carbamate pesticides was carried out by using 140 mM of acetylthiocholine, 13 mM of 5,5′-dithiobis (2-nitrobenzoic acid), temperature at 37 °C and pH of 8.0. The developed test strip cassette platform is rapid within 5 min. Based on the inhibition effect of carbaryl on acetylcholinesterase activity, the inhibition effect of carbaryl was proportional to its concentration ranging from 1 to 50 mg/L with the detection limit of 0.30 mg/L. The limit of quantitative value was determined to be 1.0 mg/L. The spiking carbaryl, the recoveries were within 96–103% and the relative standard deviations were less than 1.56%. The analysis of carbamate pesticides residual in vegetable samples gave the results in good agreement with the most widely used commercial test kit and UPLC-MS/MS method. The developed test strip cassette required only 5 min for an assay. With the simple procedures and tiny size, it showed a great promising for the developed test strip to work on-site for carbamate pesticides detection in vegetables.
Keywords: Carbamate pesticides; Carbaryl; Smartphone; Test strip cassette; Vegetables